ARM Cortex M4 cookbook : over 50 hands-on recipes that will help you develop amazing real-time applications using GPIO, RS232, ADC, DAC, timers, audio codecs, graphics LCD, and a touch screen - Fisher, Mark, Dr (Quick answers to common problems., 2016)
Annotation